Pengaruh Sosialisasi Dan Akuntabilitas Terhadap Tingkat Penerimaan Dana Zakat Pada BAZNAS Kabupaten Muaro Jambi - Seppy Indriyani; A. Tarmizi; Rohana Rohana (STEKOM PRESS, 2024)
This research aims to determine the influence of socialization and accountability on the level of receipt of zakat funds at BAZNAS Muaro Jambi regency.this research uses primary data obtained through filling out questionnaires. The sample in this study was 100 respondents. Data analysis uses validity and reliability, descriptive statistical tests, classical assumption tests and hypothesis testing using multiple linier regression methods. The data analysis method used is multiple linier regression using SPSS 27.0. the results of this research show that : (1) socialization has a significant effect on the level of receipt of zakat funds, (2) accountability has a significant effect on the level of receipt of zakat funds, (3) socialization and accountability in general together have a significant effect on the level of receipt of the zakat funds.